at school - Baretti , Sonia (Montreal Crackboom! Books, 2017)
Invites youngsters to exercise their observational skills by finding the familiar items in scenes depicting animal characters in a classroom, the schoolyard, and the lunchroom, on a field trip, at a class
Keywords: Juvenile works; School fiction